Предмет: Математика,
автор: sashabeattv
1)записать выражение -6(5-b)+3(-3b-3)-7(-8+b) без скобок
2)упростить выражение -6(5-b)+3(-3b-3)-7(-8+b)
Ответы
Автор ответа:
1
1) -6(5-b)+3(-3b-3)-7(-8+b)=-30+6b-9b-9+56-7b
2) -6(5-b)+3(-3b-3)-7(-8+b)=-30+6b-9b-9+56-7b=-10b+17
2) -6(5-b)+3(-3b-3)-7(-8+b)=-30+6b-9b-9+56-7b=-10b+17
Автор ответа:
0
спс
Похожие вопросы
Предмет: Английский язык,
автор: m00n4ik
Предмет: Русский язык,
автор: azaza1393
Предмет: История,
автор: tzuyu153
Предмет: История,
автор: mar7691026
Предмет: Математика,
автор: 11Виктория111